2023
DOI: 10.7554/elife.85289
|View full text |Cite
|
Sign up to set email alerts
|

Lipid hydroperoxides promote sarcopenia through carbonyl stress

Abstract: Reactive oxygen species (ROS) accumulation is a cardinal feature of skeletal muscle atrophy. ROS refers to a collection of radical molecules whose cellular signals are vast, and it is unclear which downstream consequences of ROS are responsible for the loss of muscle mass and strength. Here we show that lipid hydroperoxides (LOOH) are increased with age and disuse, and the accumulation of LOOH by deletion of glutathione peroxidase 4 (GPx4) is sufficient to augment muscle atrophy. LOOH promoted atrophy in a lys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…Furthermore, accumulation of LOOHs can be fatal and induce ferroptosis: iron-dependent, non-apoptotic cell death [ 60 , 61 ]. In support of this, a recent report by Eshima et al [ 62 ] demonstrated that elevated LOOH and their reactive lipid aldehyde byproducts are effectors of muscle atrophy and weakness in a disuse atrophy model. It is reasonable to conclude that the toxic effects of lipid peroxidation products might contribute to the observed decrease in muscle mass and force generation in old WT mice.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, accumulation of LOOHs can be fatal and induce ferroptosis: iron-dependent, non-apoptotic cell death [ 60 , 61 ]. In support of this, a recent report by Eshima et al [ 62 ] demonstrated that elevated LOOH and their reactive lipid aldehyde byproducts are effectors of muscle atrophy and weakness in a disuse atrophy model. It is reasonable to conclude that the toxic effects of lipid peroxidation products might contribute to the observed decrease in muscle mass and force generation in old WT mice.…”
Section: Discussionmentioning
confidence: 68%
“…Our group and others have found that overexpression of GPx4 can neutralize LOOH and/or lipid carbonyls to rescue muscle atrophy and weakness with aging, disuse, and denervation [5,30,31]. In these studies, GPx4 overexpression was germline, suggesting that these mice were protected from an increase in LOOH in all their cell-types, not just skeletal muscle [5,30].…”
Section: Introductionmentioning
confidence: 97%
“…Increases in reactive oxygen species (ROS) have been implicated as a potential cause for disuse-induced skeletal muscle atrophy [3]. Recently, our laboratory and others have identified the role of a lipid-specific form of ROS known as lipid hydroperoxides (LOOH) in disuse-induced skeletal muscle atrophy [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, proteasomal degradation is a mechanism to defuse and/or recycle damaged or obsolete proteins. Obesity is associated with insulin resistance, aberrant lipid metabolism, and mitochondrial dysfunction, all of which lead to increased reactive oxygen species and protein damage 25 , causing loss of muscle mass and function 26 . Ubiquitylation as a means for marking proteins for degradation will create higher proteasomal demand 27 .…”
Section: Discussionmentioning
confidence: 99%